Epidemiology, flexibility, growth and maturation in youth elite soccer players : prospective research leading to clinical perspectives in paediatric sports medicine - Materne, O. (Edge Hill University, 2020)
Nurturing young soccer talent and future players has become a growing and intensified interest by clubs and football associations all over the globe. In well-established European academies they focus on pursuing the enhancement of the optimal evolution of youth players to the professional team. In emergent countries they are trying to establish the cornerstone of their youth development approach aiming to compete in the future at the international level. This increased demands for success are pushing countries around the world to a combination of early specialisation and early engagement as youth elite soccer can start from as early as five years of age (Ford et al. 2012). Although, there is still no evidence of the effectiveness and long-term sports success (Read et al. 2016), the American Medical Society of Sports Medicine (DiFiori et al. 2014) and a number of researchers in youth soccer have suggested a potential psychological danger and inherent injury risks associated with this pathway (Bahr 2014; Brink et al. 2010; D. Caine et al. 2008; Jayanthi et al. 2015; Theisen et al. 2013). Recently from a survey, contrasting result has shown that specialised youth soccer players had a decreased odds of reporting previous injury than nonspecialised players (D. Frome et al. 2019). Considering that young players should be at the hub of all efforts to reduce risk of injury (Emery 2010), the foremost purpose of sports medicine research on injury risk factors, are enhancing the understanding of why injuries occur and predict who is at risk of injury (Bahr 2016). Sports injury prevention and prediction remain a complex task and even more challenging in the context of youth development, where growth and maturation occur. The assessment of sports injuries causation was developed initially based on a multifactorial model (Meeuwisse 1994) that has progressed over the time to a dynamic recursive model (Meeuwisse et al. 2007). However, due to the very complex nature of the sports injuries aetiology, the model of sports injury prevention is moving ahead to a novel concept shifting from risks factors to risk pattern recognition resulting from a chaotic interaction of a web of determinants in a non-linear system, that evolves continuously over time (Bittencourt et al. 2016; Stern et al. 2020). Despite, Bahr and Holme (2003), using a methodological approach to investigate potential risk factors for sports injuries, they highlighted the importance of studying factors that are potentially modifiable through physical training. In recent times, Bahr (2016) suggested a significant association between a screening test with injury risk and the ability of a screening test to predict future injury, emphasising that pre-participation examination is of limited interest in injury prevention to mitigate injury risk (Frisch et al. 2011). To date, appropriate coordination and supervision to ensure a healthy developmental training and competition environment as suggested by the International Olympic Committee and the American Orthopaedic Society of Sports Medicine (LaPrade et al. 2016; Mountjoy et al. 2008) has not yet been broadly applied in youth development in regards of various aspects of paediatric sports medicine. Firstly, with regards to quality dataset, diverse authors have highlighted the lack of good descriptive data in prepubescent and adolescent athletes (D. J. Caine 2010; Emery 2010; Faude et al. 2013), which is the fundamental building blocks of epidemiology and research to recognise the extent of an injury problem (van Mechelen et al. 1992). Even though longitudinal study designs have been accepted to be a keystone of observational epidemiology (Ng et al. 2012) and in the development of normative values, when age effects are to be described (P. J. O'Connor 1990), in sports medicine, longitudinal studies and analysis have not been commonly used (Finch and Marshall 2016). In team ball sports, most of the publications reported the injuries as an overall grouped result lacking to recognise multiple individual injuries (Fortington et al. 2017). Thus, the relation between injuries and reliable individual descriptive longitudinal data set, are of significant importance to bring more scientific evidence in the clinical practice of paediatric sports medicine practitioners (Emery 2010). This will provide effective benchmarking for identification of risk factors, preventive measures and clinical reasoning (D. Caine et al. 2008; D. J. Caine 2010; Emery 2010; Finch and Marshall 2016). During childhood and adolescence, individual progress through the growth and maturation process is characterised by cellular activity increasing body size toward the matured state (R. M. Malina et al. 2004). The timing (specific maturational events, e.g. the growth spurt) and tempo (rate at which maturation progress, e.g. skeletal maturity) vary considerably among individuals (R. M. Malina et al. 2004). More specifically to the scope of this thesis, growth is determined by the growth of the bones, while skeletal maturity is expressed by the degree of calcification of the ossification centres called also epiphysis (Molinari et al. 2013). There are a number of research articles regarding the contribution of growth and maturation on sports-specific technical skills and physical qualities in youth soccer (Buchheit et al. 2010; Gouvea et al. 2016; R. M. Malina et al. 2004; Philippaerts et al. 2006; Portas et al. 2016; Wong et al. 2009) . Furthermore, only a few researchers have revealed a gradual dose-anatomical response with apparent musculoskeletal deformities in players over the growth and skeletal maturation when high frequency soccer training at younger age was started (Agricola et al. 2014; Tak et al. 2015; Witvrouw et al. 2009). Surprisingly, scientific evidence on lower limb muscle flexibility changes and injury epidemiology associated with growth and maturation in youth soccer remain sparse and inconclusive with a high risk of bias (Faude et al. 2013; Stratton 2004; Swain et al. 2018). From a systematic review point of view, youth elite soccer players have a high likelihood to lose a large portion of seasonal development due to injuries, with a greater injury incidence in training than professional adult soccer players (S. Jones et al. 2019; Pfirrmann et al. 2016). The physis or growth plate is the most significant difference between the immature skeleton of children and the adult human skeleton. Consequently, the pattern of injuries in young athletes are different from adults as their growing bones can be easily overstressed by traumatic or repetitive micro-trauma events (Klenerman 1994; Wilkins 1980). The risk of pitfalls and the importance to scrutinise promptly the musculoskeletal injuries in young athletes is well recognised (Outerbridge and Micheli 1995; Perron et al. 2002). Whilst, growth related injuries can occur at any time during childhood and adolescence, they are more common during periods of rapid growth (Adirim and Cheng 2003; Antich and Brewster 1985; D. Caine 2006; Difiori 2010b). The peak incidence of fracture coincides with peak height velocity in adolescents (Blimkie et al. 1993). Physeal injuries have been reported by emergency physicians to account for between 15% and 30% of all skeletal injuries in children with 80% of these injuries occurring between the ages of 10 to 16 years. Most growth-related diseases have been well recognized a century ago (Osgood-Schlatter - 1903, Sever - 1912, Sinding-Larson & Johanson - 1921, Kolher - 1908, Iselin - 1912). Adirim and Cheng (2003) stated that children engaged in sports involving activities such as jumping and cutting, are at greater risk of growth-related diseases. However, epidemiological data on the distribution and determinants of growth plate injuries in organised sports are still lacking (D. Caine et al. 2006). In recent years, this pattern of injuries has been described as an overuse condition caused by the repetitive stress on the growth cartilage (DiFiori et al. 2014). In male adolescents from a variety of sports including soccer, overuse condition have been claimed to account for up to 46% of all injuries (Antich and Lombardo 1985; Antich and Brewster 1985).